Toxoplasma gondii seropositivity in pregnancies with normal delivery and complicated with abortion - Dinçgez Çakmak, Burcu; Dündar, Betül; Bayram, Feyza; Özgen, Gülten (The European Research Journal, 2018)
Objective: Toxoplasma infection during pregnancy may cause remarkable mortality and morbidityin fetus due to transplacental transmission. It has fetal consequences such as abortion, stillbirth and congenital malformations. In the Turkish literature, there is limited investigations evaluating the prevalence of Toxoplasma gondii among pregnancies complicated with abortion. The aim of this study is to compare the Toxoplasma seropositivity between pregnancies with normal delivery and complicated with abortion. Methods: This is a retrospective, single center study conducted between May 2015 and June 2016. We included 412 patients in the study group and 828 patients in the control group. The study group (Group 1) was compromised of pregnants whose pregnancies were complicated with abortion and the control group (Group 2) was pregnants with normal delivery. Toxoplasma IgM and IgG seropositivity were compared between two groups. Results: There was no difference between two groups in terms of sociodemographic features (p > 0.05). Toxoplasma IgM was positive in 62 (5%) patients and IgG was positive in 282 (22.9%) patients in all groups. In subgroup analysis Toxoplasma IgM was found to be positive in 27 (6.6%) patients in Group 1 and 35 (4.2%) patients in Group 2. Moreover, Toxoplasma IgG was positive in 125 (30.6%) patients in Group 1 and in 157 (19.2%) patients in Group 2. Toxoplasma IgM and Toxoplasma IgG were significantly higher in Group 1 (p = 0.023 and p = 0.016, respectively). Conclusion: We concluded that Toxoplasma seropositivity is high in our country and routine screening is essential for pregnancies. Toxoplasmosis may play a role in the etiology of abortion.